Conceptual Analysis of the Influence of Transformational Leadership Style on Employee Performance through Job Satisfaction: A Systematic Literature Review - Tanjung, Bahdin Nur; Nasution, Mutiara Akbar (Economic: Journal Economic and Business, 2025)
This study aims to conceptually analyze the relationship between transformational leadership, job satisfaction, and employee performance through a systematic literature review approach. A total of 15 scholarly articles from reputable national and international journals, particularly those indexed in Scopus, were analyzed using narrative synthesis and thematic analysis. The findings indicate that transformational leadership consistently has a positive effect on employee performance, both directly and indirectly through job satisfaction as a mediating variable. Dimensions such as idealized influence, inspirational motivation, and individualized consideration play a crucial role in fostering high levels of job satisfaction, which in turn enhance employee loyalty, motivation, and productivity. Although variations in influence were observed based on organizational and cultural contexts, the overall relationship among variables remains strong and significant. This study contributes theoretically to the development of leadership models that emphasize psychological values and provides a foundation for future quantitative research. The findings may also serve as a reference for organizations in designing leadership training programs aimed at increasing job satisfaction and employee performance.